2018
DOI: 10.1017/jfm.2018.538
|View full text |Cite
|
Sign up to set email alerts
|

Influence of plane boundary proximity on the Honji instability

Abstract: This paper presents a numerical investigation of oscillatory flow around a circular cylinder that is placed in proximity to a plane boundary that is parallel to the cylinder axis. The onset and development of the Honji instability are studied over a range of Stokes numbers ($\unicode[STIX]{x1D6FD}$) and gap-to-diameter ratios ($e/D$) at a fixed Keulegan–Carpenter number ($KC=2$). Four flow regimes are identified in the ($e/D,\unicode[STIX]{x1D6FD}$)-plane: (I) featureless two-dimensional flow, (II) stable Honj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 22 publications
1
11
0
Order By: Relevance
“…The spanwise averaged cross-sectional flow fields (not shown here) are similar to their counterparts obtained from 2-D DNS. This observation is consistent with previous findings in literature of oscillatory flow past cylinder(s)[14,[16][17][18]. Since the primary objective of this study is on CD and CM and 3-D simulations at high β constitute a daunting task computationally, the following discussions are based on the results from 2-D DNS.…”
supporting
confidence: 88%
“…The spanwise averaged cross-sectional flow fields (not shown here) are similar to their counterparts obtained from 2-D DNS. This observation is consistent with previous findings in literature of oscillatory flow past cylinder(s)[14,[16][17][18]. Since the primary objective of this study is on CD and CM and 3-D simulations at high β constitute a daunting task computationally, the following discussions are based on the results from 2-D DNS.…”
supporting
confidence: 88%
“…The existence of inflection points in the velocity profiles of a laminar Stokes boundary layer at different phases shown in figure 4 is directly responsible for the destabilisation of the negative vortex layer, as indicated in figure 3(a,b) at t/T = 0.469. The boundary layer separation and vortex shedding are observed in figure 3(c), possibly due to the large size of roughness element h = 1 that acts like a bluff body attached to the wall (Xiong et al 2018a). The corrugation of the positive vortex layer and the further formation of a counter-rotating vortex pair after the flow reversal, which are observed at t/T = 0.562 in figure 3, resulted from the nonlinear evolution of the inflection-point instability, as suggested by Scandura (2013).…”
Section: Vortex Tubesmentioning
confidence: 99%
“…The present blockage ratios are 2 % and 1 % respectively for K ≤ 3 and K > 3, which are judged to be adequate based on the experiences reported in the literature. For instance, previous investigations on Honji instabilities by An, Cheng & Zhao (2011), Suthon & Dalton (2011) and Xiong et al (2018a) employed domain sizes with blockage ratios of 6.67 %, 2.5 % and 1.67 % respectively. For studies associated with quantifying flow regimes on multiple cylinders, 1.67 % and 3.33 % were used for two circular cylinders (Zhao & Cheng 2014) and the range 2 %-2.91 % was selected for a cluster of four cylinders (Tong et al 2015;Ren et al 2019).…”
Section: Numerical Methods and Computational Domainmentioning
confidence: 99%
“…Previous studies (e.g. An et al 2011;Xiong et al 2018a) showed that good correlations exist between L z and the characteristic length of 3-D structures (λ), which can be estimated according to the empirical formula proposed by Sarpkaya (2002) as, λ/D = 22β −3/5 ( λ ∼ 0.34D at β = 1035). Xiong et al (2018a) suggested that a ratio of L z /λ ≈ 3 and N z = 18 are generally adequate in resolving spanwise structures of oscillatory flows.…”
Section: A2 Spanwise Mesh Selectionsmentioning
confidence: 99%
See 1 more Smart Citation